(untitled) (Journal of Human Sciences, 2026)
This study aims to explore the factors influencing academic achievement in the Arabic language subject among students at the basic education stage in Misrata City. To achieve the objectives of the study, the researcher developed a questionnaire based on the instrument prepared by Abdel-Razek (2010), comprising four main categories of factors, each containing a set of items related to that specific factor. The validity of the questionnaire was verified through expert review and by calculating the internal consistency of the items. The instrument was then distributed to a sample of 100 Arabic language teachers (both male and female) working in various basic education schools across Misrata City. The participants were selected using a random sampling method. To ensure the reliability of the questionnaire, it was also administered to a separate random sample of Arabic language teachers outside the main study sample. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings of the study indicated that all the factors identified are influential in students’ academic achievement in the Arabic language subject. Teacher-related factors were ranked at a high level, with a mean score of 2.66. In contrast, factors related to teaching methods and instructional materials, the prescribed textbook, as well as student-related and family-related circumstances were classified at a moderate level, with mean scores of 2.23, 2.32, and 2.24, respectively.